India's Neighbourhood First Policy - Pant, Bhuwaneswor (Journal of Tikapur Multiple Campus, 2018)
After assuming post of prime-minister of India, Narendra Modi hinted that his foreign policy will actively focus on improving ties with India’s immediate neighbours, a policy that has since been termed the neighbourhood first policy. India’s Neighbourhood first Policy indicating four things: India will be giving political and diplomatic priorities to her and immediate neighbours and Indian Ocean Island states, India to provide all essential requirements of her immediate neighbours as needed by them, to promote greater connectivity and integration in the Indian subcontinent to ensure a free flow of goods and services, people, capital etc., and to establish an India-led regionalism in the neighbourhood. The neighbouring countries had tried to check and restrict India geopolitically and geo- economically through the overt or covert strategic relationships with the extra-regional powers. China’s assertive, and often aggressive, behaviour has been viewed as a huge challenge for India because it opens up the likelihood of China dominating India’s immediate neighbourhood. The “neighborhood first” policy is the striking feature of Modi government’s diplomatic approach. In his government’s strategic imagination, India’s relations with neighboring countries must receive topmost priority. If India does not resolve its differences with its small neighbors, it will only pave the way for China to exert growing influence in the region.